-2x - 6 < = 1
-2x < = 1 + 6
-2x < = 7...change the inequality sign when dividing by a negative number
x > = -7/2
x > = - 3.5
the one that does not satisfy the inequality is : -4...because it is less then -3.5
Answer:
x=y
y=x
y=2
x=2
(3)(2)
3 times 2 is 6
Step-by-step explanation:
<h3>
Answer: w^2 + 3w - 10</h3>
===============================================
Work Shown:
Let x = w-2
This will allow us to replace the (w-2) with x to get...
(w-2)(w+5)
x(w+5)
x*w + x*5 ... distribute
w(x) + 5(x)
Now replace x with w-2 and distribute again
w(x) + 5(x)
w(w-2) + 5(w-2)
w*w + w*(-2) + 5*w + 5*(-2)
w^2 - 2w + 5w - 10
w^2 + 3w - 10
Answer: #13 you need to know that the sides are equal. #14 (7,6)
Step-by-step explanation: #14 in picture
Answer:
Step-by-step explanation:
f^-1(x)=x/2+3